2006
DOI: 10.1111/j.1447-073x.2006.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Double innervation of the anterior belly of the digastric muscle

Abstract: We came across a very rare case in which the anterior belly of the digastric muscle was innervated by the twigs of the facial nerve in addition to those of the mylohyoid nerve. The anomaly was discovered in the cadaver of an 84-year-old Japanese male bequeathed for a training seminar in gross anatomy at Kumamoto University in 2003. One twig issued from the marginal mandibular branch of the facial nerve and entered the central region of the anterior belly of the digastric muscle on the lower surface. The other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The mylohyoid nerve of the inferior alveolar nerve of the mandibular nerve of the trigeminal nerve innervates the anterior belly of the digastric muscle, and the facial nerve innervates the posterior belly of the digastric muscle [10]. However, there are some reported cases that the anterior belly of the digastric muscle was innervated by the branches of the facial nerve in addition to the mylohyoid nerve [1415]. Furthermore, Kawai et al [15] observed that when the branches of the facial nerve innervate the anterior belly of the digastric muscle, they seemed to be specifically the branches of the stylohyoid nerve.…”
Section: Nerve Innervationmentioning
confidence: 99%
“…The mylohyoid nerve of the inferior alveolar nerve of the mandibular nerve of the trigeminal nerve innervates the anterior belly of the digastric muscle, and the facial nerve innervates the posterior belly of the digastric muscle [10]. However, there are some reported cases that the anterior belly of the digastric muscle was innervated by the branches of the facial nerve in addition to the mylohyoid nerve [1415]. Furthermore, Kawai et al [15] observed that when the branches of the facial nerve innervate the anterior belly of the digastric muscle, they seemed to be specifically the branches of the stylohyoid nerve.…”
Section: Nerve Innervationmentioning
confidence: 99%